(untitled) (Environmental Smoke, 2020)
The Veterinarian must be aware of the pastures and their handling, as the high quality pastures will contribute to an excellent nutrition of the animals. Within this logic, soil is an essential natural resource for the survival of animals, since ecosystems contribute to the growth of plants and to the regulation of water flow in the environment, functioning as an environmental buffer, in the formation, attenuation and degradation of compounds natural. Composting is the process of controlled degradation of organic waste, which is a process in which it seeks to reproduce ideal conditions of humidity, oxygen and nutrients, especially carbon and nitrogen, to favor and accelerate the degradation of waste in a safe manner, avoiding the attraction of disease vectors and eliminating pathogens. Thus, knowing these environmental contributions, will favor in the guidelines that the veterinarian should pass on to the country man, aiming to have a well-nourished herd and with consequent lesser animal convalescence.